MMP-3 and TIMP-1 as prognostic biomarkers in VZV-induced retinal necrosis - Wang, Zhujian; Liu, Yu; Zhou, Min; Lei, Boya; Chang, Qing; Cao, Wenjun (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveAcute retinal necrosis (ARN) caused by varicella-zoster virus (VZV) is associated with changes in specific proteins in the eye’s fluid, particularly matrix metalloproteinase-3 (MMP-3), an enzyme that breaks down tissue structures, and tissue inhibitor of metalloproteinase-1 (TIMP-1), which regulates MMP activity. This study aims to investigate how these proteins correlate with the progression of ARN.MethodsWe analyzed aqueous humor samples from 33 patients with ARN and 23 control patients with virus-negative uveitis. MMP-3 levels were measured using immunoturbidimetry, and TIMP-1 levels were determined using an enzyme-linked immunosorbent assay. We examined the relationships between these protein levels and clinical findings using statistical correlation methods.ResultsMMP-3, TIMP-1 were significantly higher in the aqueous humor of ARN patients compared to the controls (P<0.0001). Correlation analysis revealed a significant correlation between MMP-3 levels and TIMP-1 (r = 0.460, P = 0.007). The upregulation of MMP-3 and TIMP-1 was found to parallel VZV DNA load and IL-6 levels. Additionally, they exhibited negative correlation with best corrected visual acuity (BCVA) and positive correlation with the percentage of active retinal necrosis area.MMP-3 was markedly enhanced in all 14 cases of retinal detachment (RD), whereas TIMP-1 levels were significantly reduced in the same cohort of eyes. Patients with initial higher TIMP-1 levels have a significantly increased risk of developing RD, with a hazard ratio (HR) of 3.152 (95% CI, 1.082-9.18).ConclusionThe imbalance between MMP-3 and TIMP-1 may play a critical role in the development and severity of ARN. Measuring these proteins in the eye’s aqueous humor could be valuable for assessing disease progression and guiding treatment strategies, potentially improving outcomes for patients with virus-induced retinal diseases.